2014
DOI: 10.1186/1471-2229-14-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of CBL and CIPK gene families in canola (Brassica napus L.)

Abstract: BackgroundCanola (Brassica napus L.) is one of the most important oil-producing crops in China and worldwide. The yield and quality of canola is frequently threatened by environmental stresses including drought, cold and high salinity. Calcium is a ubiquitous intracellular secondary messenger in plants. Calcineurin B-like proteins (CBLs) are Ca2+ sensors and regulate a group of Ser/Thr protein kinases called CBL-interacting protein kinases (CIPKs). Although the CBL-CIPK network has been demonstrated to play cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
109
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(122 citation statements)
references
References 72 publications
10
109
0
3
Order By: Relevance
“…Conventional approaches along with more recent genomic technology based tools are driving the advances in this field. While priority crops like corn, 37 soybean, 38 rice, 39 wheat, 40 and canola 41,42 along with Arabidopsis model system [43][44][45][46] have witnessed significant recent advances in drought research including the application of molecular breeding tools in new varietal development; so far very limited progress has been made in the flax crop. To address this gap, in the present study, we performed genome-wide gene expression analysis to identify genetic programs associated with drought in flax.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional approaches along with more recent genomic technology based tools are driving the advances in this field. While priority crops like corn, 37 soybean, 38 rice, 39 wheat, 40 and canola 41,42 along with Arabidopsis model system [43][44][45][46] have witnessed significant recent advances in drought research including the application of molecular breeding tools in new varietal development; so far very limited progress has been made in the flax crop. To address this gap, in the present study, we performed genome-wide gene expression analysis to identify genetic programs associated with drought in flax.…”
Section: Introductionmentioning
confidence: 99%
“…The CIPK gene family has been analyzed in Arabidopsis 2122, poplar ( Populus trichocarpa )22, maize ( Zea mays )23, rice ( Oryza sativa )24, and canola ( Brassica napus )25. These studies reported that the CIPK gene family could be divided into an intron-rich clade and an intron-poor clade, in which a subgroup in Arabidopsis , maize, rice and canola CIPK genes were induced by drought23242526.…”
mentioning
confidence: 99%
“…These studies reported that the CIPK gene family could be divided into an intron-rich clade and an intron-poor clade, in which a subgroup in Arabidopsis , maize, rice and canola CIPK genes were induced by drought23242526. Although soybean ( Glycine max var.…”
mentioning
confidence: 99%
“…To date, CIPK family genes have been identified in Arabidopsis, rice, canola, maize and wheat, and some CIPKs have been functionally characterized [59]. The AtCBL4-CIPK24 (SOS3-SOS2) complex specifically regulates Na + efflux by the Na + /H + antiporter and enhances salt tolerance [10, 11].…”
Section: Introductionmentioning
confidence: 99%